ГЛОБАЛЛАШУВ ДАВРИДА МАЪНАВИЙ ВА МАФКУРАВИЙ ХАВФСИЗЛИКНИ ТАЪМИНЛАШДА ОММАВИЙ АХБОРОТ ВОСИТАЛАРИНИНГ ТРАНСФОРМАЦИЯЛАШИШ ЖАРАЁНИ - Атамуратов, М.У. (SCIENCE and SOCIETY, 2024)
This article analyzes the question that the necessary reform in Uzbekistan in the sphere of transforming the political views of the Uzbek people about spiritual and ideological threats is the regulation of any form of relationship with the media, journalism and blogging activities, as well as with data in the information world.
Keywords: globalization; modernization; media; spiritual security; ideological security; political security; information attack; national idea; transformation; evil forces; mass culture; information technology; bloggers; social networks